Sex‐Based Disparities in Liver Transplant Rates in the United States - Mathur, A. K.; Schaubel, D. E.; Gong, Qi; Guidinger, M. K.; Merion, R. M. (American journal of transplantation, 2011)
We sought to characterize sex‐based differences in access to deceased donor liver transplantation. Scientific Registry of Transplant Recipients data were used to analyze n = 78 998 adult candidates listed before (8/1997–2/2002) or after (2/2002–2/2007) implementation of Model for End‐Stage Liver Disease (MELD)‐based liver allocation. The primary outcome was deceased donor liver transplantation. Cox regression was used to estimate covariate‐adjusted differences in transplant rates by sex. Females represented 38% of listed patients in the pre‐MELD era and 35% in the MELD era. Females had significantly lower covariate‐adjusted transplant rates in the pre‐MELD era (by 9%; p < 0.0001) and in the MELD era (by 14%; p < 0.0001). In the MELD era, the disparity in transplant rate for females increased as waiting list mortality risk increased, particularly for MELD scores ≥15. Substantial geographic variation in sex‐based differences in transplant rates was observed. Some areas of the United States had more than a 30% lower covariate‐adjusted transplant rate for females compared to males in the MELD era. In conclusion, the disparity in liver transplant rates between females and males has increased in the MELD era. It is especially troubling that the disparity is magnified among patients with high MELD scores and in certain regions of the United States. Geographically distinct, sex‐based disparities in access to liver transplantation from the waiting list are evident in the United States that persist despite accounting for numerous gender‐relevant clinical factors, and suggest gender‐based inequity in care for patients with liver disease. See editorial by Lai and Feng on page 1353.